Diffusion tensor imaging detects chronic microstructural changes in white and gray matter after traumatic brain injury in rat - Laitinen, Teemu; Sierra, Alejandra; Bolkvadze, Tamuna; Pitkänen, Asla; Gröhn, Olli (Frontiers in Neuroscience, 2015)
Traumatic brain injury (TBI) is a major cause of disability and death in people of all ages worldwide. An initial brain injury caused by external mechanical forces triggers a cascade of tissue changes that lead to a wide spectrum of symptoms and disabilities, such as cognitive deficits, mood or anxiety disorders, motor impairments, chronic pain, and epilepsy. We investigated the detectability of secondary injury at a chronic time-point using ex vivo diffusion tensor imaging (DTI) in a rat model of TBI, lateral fluid percussion (LFP) injury. Our analysis of ex vivo DTI data revealed persistent microstructural tissue changes in white matter tracts, such as the splenium of the corpus callosum, angular bundle, and internal capsule. Histologic examination revealed mainly loss of myelinated axons and/or iron accumulation. Gray matter areas in the thalamus exhibited an increase in fractional anisotropy associated with neurodegeneration, myelinated fiber loss, and/or calcifications at the chronic phase. In addition, we examined whether these changes could also be detected with in vivo settings at the same chronic time-point. Our results provide insight into DTI detection of microstructural changes in the chronic phase of TBI, and elucidate how these changes correlate with cellular level alterations.